An NTFA-based homogenization framework considering softening effects - Ju, X.; Mahnken, Rolf (Mechanics of Materials)

Design of voltage controlled oscillators (VCOs) in D-band and their phase noise measurements using frequency down-conversion - Ali, U.; Bober, M.; Thiede, Andreas (2016 11th European Microwave Integrated Circuits Conference (EuMIC))

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

The International Liquid Crystal Society 1990–2015 - Dunmur, David; Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Comparison of Cost and Complexity for Various 16-QAM Transmitter Structures in Coherent Optical Systems - Al-Bermani, Ali; Noé, Reinhold (NEXT-GENERATION OPTICAL COMMUNICATION: COMPONENTS, SUB-SYSTEMS, AND SYSTEMS V)

Die Welt 'im schönsten Fall' - Umbruchs- und Katastrophenszenarien im Werk Angela Krauß - Morrien, Rita (Umwelt - sozial, kulturell, ökologisch. Zur Darstellung von Zeitgeschichte in deutschsprachiger Gegenwartsliteratur)

Spuren des Dialogs - literatur- und kulturwissenschaftliche Überlegungen zum Thema Dialog. 50 Jahre diplomatische Beziehungen zwischen Deutschland und Israel - Morrien, Rita (Traces of Dialogue. Symposion and exhibition 2015 between Israel/Rishon LeZion and Germany/Münster)

LiNbO3-Based Endless Optical Polarization Control The Photonic Alternative to Coherent Electronics - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Time-resolved Mueller matrix measurement and polarization scrambler characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

LiNbO3-based endless optical polarization control - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

Accelerated Testing of Polarization-Tracking Receiver Using Polarization Scrambler with Peaked Speed Distribution - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (Photonic Networks; 17. ITG-Symposium; Proceedings of)

Catalani, Angelica - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Tetrazzini, Luisa - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Patti, Adelina - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Pasta, Giuditta - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Lind, Jenny - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Gender - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Gar keine Stimme? Wilhelmine Schröder-Devrient, Wagner und das Singen - Grotjahn, Rebecca (Bühnenrollen und Identitätskonzepte – Karrierestrategien von Künstlerinnen im Theater des 19. Jahrhunderts)

Der Wundersmann: Johann Sebastian Bach und die Kantate Wer nur den lieben Gott lässt walten BWV 93 - Grotjahn, Rebecca ("Ei, dem alten Herrn zoll’ ich Achtung gern'." Festschrift für Joachim Veit zum 60. Geburtstag)

Highly functionalized alkenes produced from base-free organocatalytic Wittig reactions: (E)-3-benzylidenepyrrolidine-2,5-dione, (E)-3-benzylidene-1-methylpyrrolidine-2,5-dione and (E)-3-benzylidene-1-tert-butylpyrrolidine-2,5-dione - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section C Structural Chemistry)
The Wittig reaction is a fundamental transformation for the preparation of alkenes from carbonyl compounds and phosphonium ylides. The ylides are prepared prior to the olefination step from the respective phosphonium salts by deprotonation utilizing strong bases. A first free-base catalytic Wittig reaction for the preparation of highly functionalized alkenes was based on tributylphosphane as the catalyst. Subsequently we developed a system employing a phospholene oxide as a pre-catalyst and trimethoxysilane as reducing agent which operates under milder conditions. The title compounds, ( E )-3-benzylidenepyrrolidine-2,5-dione, C 11 H 9 NO 2 , (I), the methylpyrrolidine derivative, C 12 H 11 NO 2 , (II), and the tert- butylpyrrolidine derivative, C 15 H 17 NO 2 , (III), have been synthesized by base-free catalytic Wittig reactions. In the crystal of (I), molecules are linked into centrosymmetric dimers via pairs of N—H...O hydrogen bonds. Furthermore, in the crystal structure of (III), there are two molecules in the asymmetric unit, whereas in (I) and (II), only one molecule is present.
Keywords: Materials Chemistry; Inorganic Chemistry; Physical and Theoretical Chemistry; Condensed Matter Physics